Lipidomics as a diagnostic tool of the metabolic and physiological state of managed whales: A correlation study of systemic metabolism - Tang, Chuan‐Ho; Lin, Ching‐Yu; Tsai, Yi‐Lun; Lee, Shu‐Hui; Wang, Wei‐Hsien (Zoo biology, 2018)
Integrating multifactor blood analysis is a key step toward a precise diagnosis of the health status of marine mammals. Variations in the circulating lipid profile reflect changes in the metabolism and physiology of an individual. To demonstrate the practicability of lipid profiling for physiological assessment, the phosphorylcholine‐containing lipids in the plasma of long‐term managed beluga whales (Delphinapterus leucas) were profiled using a lipidomics methodology. Using a multivariate analysis, the mean corpuscular volume, cholesterol, potassium, and γ‐glutamyltranspeptidase levels were well modeled with the lipid profile of the female whales. In the models, the correlated lipids provided information about blood parameter‐related metabolism and physiological regulation, in particular relating to cholesterol and inflammation. In the males, the levels of cholesterol, triglycerides, blood urea nitrogen, creatinine, plasma iron, and segmented neutrophil were well modeled with the lipid profile. In addition to providing information about the related metabolism and regulation, through a cross‐linked analysis of the blood parameters, the correlated lipids indicated a parallel regulation involved in the energy metabolism of the male whales. Lipidomics as a method for revealing the context of physiological change shows practical potential for the health care of managed whales.